Sinergy of Community Participation, Government Support and Environmental Awareness on Local Wisdom Based Sustainable Ecotourism Village - Aji Prabowo; Montaris Silaen; Desyana Putri (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
Local wisdom-based tourism plays an important role in sustainable development; however, Tomok Tourism Village in Samosir still faces challenges such as low community participation, limited government support, and a lack of environmental awareness. This study aims to analyze the roles of community participation, government support, and environmental awareness in fostering local wisdom-based sustainable ecotourism in Tomok Tourism Village, Samosir. A mixed-methods approach was employed, combining quantitative surveys of 100 respondents analyzed using SEM-PLS with qualitative interviews and field observations involving 10 informants to capture socio-cultural contexts. Quantitative results reveal that community participation has a significant and dominant effect on sustainable ecotourism (path coefficient = 0.495; p-value 0.000 < 0.05), while environmental awareness also shows a significant positive influence (path coefficient = 0.362; p-value 0.000 < 0.05). In contrast, government support, though positive in direction, does not significantly affect sustainability (path coefficient = 0.148; p-value 0.208 > 0.05). Qualitative findings reinforce these results by showing that local communities actively participate in tourism management based on a strong sense of ownership and cultural values, while government involvement is often limited to regulatory and short-term assistance. Respondents also emphasized that environmental awareness among both residents and visitors has begun to improve through collective initiatives to maintain cleanliness and reduce plastic waste. Overall, sustainable ecotourism in Tomok is primarily driven by active community involvement and environmental consciousness, while the government’s role remains suboptimal. The study suggests the need to strengthen community capacity, enhance environmental education, and reposition the government’s role from regulator to facilitator in achieving sustainable ecotourism.